PENGARUH MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING BERBANTUAN MEDIA MAPLE 11 TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Syazali, Muhamad (Al-Jabar: Jurnal Pendidikan Matematika, 2015)
Lack of mathematical problem solving ability of students in Bandar Lampung MAN 2 due learners trouble completing math problems and students rarely ask questions or express ideas workmanship. This study aims to determine the effect of mathematical problem solving ability of student who take the learning by using the Creative Problem Solving learning model the students who take the Creative Problem Solving learning model which aided media Maple 11 and students who follow conventional teaching methods conducted by researchers at the students of class XI the MAN 2 Bandar Lampung.This research is a quantitative type of experimentation with Quasy Experimental Design. In this study a total population of 121 students with sampling techniques in this study using a sample saturated. There are significant CPS assisted learning Maple 11 on problem solving skills of learners.